Loganathan and Sivakumars Baum Test a psychodiagnostic tool to identify internet addiction - Indradevi P. Marimuthu (Tanjong Malim, 2022)
Loganathan and Sivakumars Baum Test a psychodiagnostic tool to identify internet addiction by Indradevi P. Marimuthu